Β Blockers in heart failure: a comparison of a vasodilating β blocker with metoprolol. Issue 1 (1st January 1998) - Sanderson, J E; Chan, S K W; Yu, C M; Yeung, L Y C; Chan, W M; Raymond, K; Chan, K W; Woo, K S
Abstract : Objective: To determine whether a third generation vasodilating β blocker (celiprolol) has long term clinical advantages over metoprolol in patients with chronic heart failure. Design: A double blind placebo controlled randomised trial. Setting: University teaching Hospital. Patients: 50 patients with stable chronic heart failure (NYHA class II-IV) due to idiopathic dilated, ischaemic, or hypertensive cardiomyopathy, with left ventricular ejection fraction < 0.45. Interventions: Celiprolol 200 mg daily (n = 21), metoprolol 50 mg twice daily (n = 19), or placebo (n = 10) for three months with a four week dose titration period. After the double blind period, patients entered an open label study (with placebo group receiving β blockers) and were assessed after one year. Main outcome measures: Clinical response, efficacy, and tolerance were assessed by the Minnesota heart failure symptom questionnaire, six minute walk test, Doppler echocardiography (systolic and diastolic function), radionuclide ventriculography, and atrial and brain natriuretic peptides measured at baseline and after three months. Results: In the metoprolol group at 12 weeks v baseline there was a 47% reduction in symptom score (p < 0.001), improvement of NYHA class (mean (SEM), 2.6 (0.12) to 1.9 (0.13), p = 0.001), exercise distance (1246 (54) to 1402 (52) feet, p < 0.001), and left ventricular ejection fraction (26.9(3.1)% to 31(3.0)%, p = 0.016), and a fall in heart rate (resting, 79 (3) to 62 (3) beats/min, p < 0.001). In the celiprolol group there was a 38% reduction in symptom score (p = 0.02), less improvement in exercise distance (1191 (55) to 1256 (61) feet, p = 0.05), and no significant changes in NYHA class, left ventricular ejection fraction, or heart rate. Mortality at one year was 11% in metoprolol and 19% in the celiprolol group, and symptomatic improvement was maintained in the survivors. Conclusions: Both drugs were well tolerated but the vasodilator properties of celiprolol do not seem to provide any obvious additional benefit in the long term treatment of heart failure.